Genetic variation of endangered Jankowski’s Bunting (Emberiza jankowskii): High connectivity and a moderate history of demographic decline - Huang, Long; Feng, Guochen; Li, Dan; Shang, Weiping; Zhang, Lishi; Yan, Rongfei; Jiang, Yunlei; Li, Shi (Frontiers in Ecology and Evolution, 2023)
Continued discovery of “mismatch” patterns between population size and genetic diversity, involving wild species such as insects, amphibians, birds, mammals, and others, has raised issues about how population history, especially recent dynamics under human disturbance, affects currently standing genetic variation. In this study, we used a mitochondrial DNA fragment and 15 microsatellite markers to analyze the population connectivity and demographic history of Jankowski’s Bunting (Emberiza jankowskii) in eastern Inner Mongolia. The results suggested that large historical effective population size, as well as severe but slow population decline, may partially explain the high observable genetic diversity. Comparison of historical (over the past 4Ne generations) and contemporary (1-3 generations) gene flow indicated that the connectivity between five local populations was only marginally affected by landscape changes. However, the time-lag effects on the genetic response to recent environmental changes is a reminder to be cautious about the current genetic characteristics of this species. Where possible, factors influencing genetic variation should be integrated into a systematic framework for conducting robust population health assessments. Given the small contemporary population size, inbreeding, and ecological specialization, we recommend that habitat protection be maintained to maximize the genetic diversity and population connectivity of Jankowski’s Bunting.